2009
DOI: 10.1002/cyto.a.20828
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent high‐content imaging allows the discrimination and quantitation of E‐LDL‐induced lipid droplets and Ox‐LDL‐generated phospholipidosis in human macrophages

Abstract: Macrophage foam cells formed during uptake of atherogenic lipoproteins are a hallmark of atherosclerotic lesion development. In this study, human macrophages were incubated with two prototypic atherogenic LDL modifications enzymatically degraded LDL (E-LDL) and oxidized LDL (Ox-LDL) prepared from the same donor LDL. To detect differences in macrophage lipid storage, fluorescent high-content imaging was used. Lipid droplets were stained using Bodipy 493/503, and the fluorescent phospholipid probe NBD-PE was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Accordingly, high-content imagining techniques could be developed to specifically screen for additional chemical material that promotes similar effects on the NS5A distribution. Indeed, such analyses were previously employed to examine the behaviors of LDs in response to various stimuli (15,41,65).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, high-content imagining techniques could be developed to specifically screen for additional chemical material that promotes similar effects on the NS5A distribution. Indeed, such analyses were previously employed to examine the behaviors of LDs in response to various stimuli (15,41,65).…”
Section: Discussionmentioning
confidence: 99%
“…Although several fixation methods for the study of lipid droplets by immunofluorescence microscopy have been tested, 54 fixation with paraformaldehyde, which was performed here, has been described as the method of choice, because cells retain their lipid content, and the structure of cytoplasmic neutral lipid deposits is unaffected by this fixation method. 55,56 Together, these assays initially suggested that the somatic reprogramming to stemness activates the expression of pivotal lipogenic enzymes (i.e., ACACA and FASN) and actively promotes the conversion and storage of excess fatty acids to triglycerides, which accumulate as lipid droplet-like neutral lipid depots. As a preliminary test of this counterintuitive hypothesis, bona fide iPS colonies maintained in an undifferentiated state were cultured in the presence of bisphenol A diglycidyl ether (BADGE), a synthetic antagonist of the prime inducer of adipogenesis, PPARgamma, which has been shown to regulate LIF-induced growth and self-renewal of mouse embryonic stem (ES) cells.…”
Section: The Mitochondrial H + -Atp Synthase and The Lipogenic Switchmentioning
confidence: 99%
“…Neutral lipids stored in LDs were visualized by fluorescence microscopy using BODIPY 493/503 dye (Molecular Probes, Life technologies, Monza, Italy) [27]. Cells grown on coverslips were rinsed with phosphate-buffered saline (PBS) pH 7.4 and fixed with 4% paraformaldehyde in PBS for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%